Leaf size of woody dicots predicts ecosystem primary productivity. (6th April 2020) - Li, Yaoqi; Reich, Peter B.; Schmid, Bernhard; Shrestha, Nawal; Feng, Xiao; Lyu, Tong; Maitner, Brian S.; Xu, Xiaoting; Li, Yichao; Zou, Dongting; Tan, Zheng‐Hong; Su, Xiangyan; et al.
Abstract: A key challenge in ecology is to understand the relationships between organismal traits and ecosystem processes. Here, with a novel dataset of leaf length and width for 10 480 woody dicots in China and 2374 in North America, we show that the variation in community mean leaf size is highly correlated with the variation in climate and ecosystem primary productivity, independent of plant life form. These relationships likely reflect how natural selection modifies leaf size across varying climates in conjunction with how climate influences canopy total leaf area. We find that the leaf size‒primary productivity functions based on the Chinese dataset can predict productivity in North America and vice‐versa. In addition to advancing understanding of the relationship between a climate‐driven trait and ecosystem functioning, our findings suggest that leaf size can also be a promising tool in palaeoecology for scaling from fossil leaves to palaeo‐primary productivity of woody ecosystems. Abstract : Based on leaf size and distribution data for 10 480 woody dicots in China and 2374 in North America, we found that leaf size of woody dicots well predicts ecosystem primary productivity both in China and North America, and its independent and direct effects on primary productivity is higher than (or in a few cases comparable to) those of climate, soil characteristics and leaf area index. Our results suggest that leaf size provides a promising surrogate to reconstruct palaeo‐primary productivity of terrestrial woody ecosystems based on fossil leaf deposits.